JAMINAN BANK DALAM PENGAJUAN KEBERATAN PUTUSAN KPPU MENURUT PERATURAN PEMERINTAH NOMOR 44 TAHUN 2021 (Perspektif Keadilan) - Abqari Muhammad Al Fatih (2023)
Provisions for bank guarantee norms as a formal requirement for filing objections to KPPU decisions in Government Regulation Number 44 of 2021 have changed the procedures for handling business competition cases at the Commercial Court and Supreme Court. Setting these formal requirements is considered to impede business actors' rights to obtain justice when examining the formal and material aspects of the business competition cases they face. This study uses a normative juridical method that examines Government Regulation Number 44 of 2021, particularly relating to bank guarantees as a formal requirement for legal remedies for objections and cassation in cases of business competition. The results obtained indicate the formation of bank guarantee norms as a formal requirement for filing objections and legal remedies, aimed at providing guarantees of justice for reporters or the public, business actors, and KPPU for the results of examinations and decisions of disputed cases to realize legal certainty in enforcing business competition law in Indonesia.